The INSPIRE Comparative Cost Study: 12-Month Health Economic and Clinical Outcomes Associated with Hysterectomy, Myomectomy, and Treatment with the Sonata System - Brooks E; Mihalov L; Delvadia D; Hudgens J; Mama S; Makai GE; Yuen MW; Little CA; Bauserman RL; Zambelli-Weiner A; Levine DJ (Dove Medical Press, 2020)
Elizabeth Brooks,1 Linda Mihalov,2 Dipak Delvadia,3 Joseph Hudgens,4 Saifuddin Mama,5 Gretchen E Makai,6 Matt W Yuen,1 Carter A Little,1 Robert L Bauserman,1 April Zambelli-Weiner,1 David J Levine7 1TTi Health Research & Economics, Westminster, MD, USA; 2Benaroya Research Institute at Virginia Mason Medical Center, Seattle, WA, USA; 3Drexel University College of Medicine, Philadelphia, PA, USA; 4Eastern Virginia Medical School, Norfolk, VA, USA; 5Cooper Medical School of Rowan University, Camden, NJ, USA; 6Christiana Care Health System, Newark, DE, USA; 7Mercy Clinical Minimally Invasive Gynecology, St. Louis, MO, USACorrespondence: Elizabeth BrooksTTi Health Research & Economics, 1231 Tech Court, Suite 201, Westminster, MD 21157, USATel +1800-580-2990Fax +1888-800-580-2990Email ebrooks@tti-research.comPurpose: The INSPIRE study compared perioperative and 12-month health economic and clinical outcomes associated with hysterectomy, myomectomy, and sonography-guided transcervical fibroid ablation (TFA) using the Sonata® system.Patients and Methods: Cost and health care resource utilization (HCRU) data for TFA were obtained from a prospective, multicenter, single-arm clinical trial. Data for hysterectomy and myomectomy arms were derived from the Truven Health MarketScan commercial payer claims database. The Truven data was used to determine health economic outcomes and costs for the hysterectomy and myomectomy arms. For each arm, payer perspective costs were estimated from the available charge and HCRU data.Results: TFA with Sonata had significantly lower mean length of stay (LOS) of 5 hrs versus hysterectomy (73 hrs) or myomectomy (79 hrs; all p< 0.001). The average payer cost for TFA treatment, including the associated postoperative HCRU was $8,941. This was significantly lower compared to hysterectomy ($24,156) and myomectomy ($22,784; all p< 0.001). In the TFA arm, there were no device- or procedure-related costs associated with complications during the peri- or postoperative time frame. TFA subjects had significantly lower costs associated with complications, prescription medications, and radiology.Conclusion: Compared to hysterectomy and myomectomy, TFA treatment with the Sonata system was associated with significantly lower index procedure cost, complication cost, and LOS, contributing to a lower total payer cost through 12 months.Keywords: uterine fibroids, health care resource utilization, payer perspective analysis, transcervical fibroid ablation, TFA, uterine preserving treatment